Short-term sublethal (sediment and aquatic roots of floating macrophytes) assays with a tropical chironomid based on postexposure feeding and biomarkers - Moreira-Santos, Matilde
This study proposes assays with a freshwater chironomid, Chironomus xanthus, distributed over South America, based on subindividual (acetylcholinesterase activity) and individual (survival and postexposure feeding) level endpoints. Sediment and aquatic-rooted floating macrophyte assays were developed, due to the importance of both substrates for toxicant exposure in subtropical/tropical environments. Assays were evaluated under realistic exposure scenarios by simulating a runoff over an agricultural field dosed with deltamethrin. In situ assays were performed within microcosms to discriminate the effects of deltamethrin from those of additional potential stress factors (organism handling and caging, microcosms, use of aquatic roots, and runoff per se). A laboratory sediment assay based on feeding was conducted with samples from the microcosms. In all assays, both sublethal endpoints were responsive to deltamethrin and more sensitive than survival. Survival and feeding were more sensitive in situ than in the laboratory. In the in situ sediment assays, both sublethal endpoints were within a similar range of sensitivity; they were significantly inhibited as of the lowest Decis dose, from approximately 20 to 70%. In situ feeding was more sensitive in the sediment than in the macrophyte assay, where it was inhibited significantly only at the two highest Decis doses (up to similar to 60%). Larval performance was not influenced significantly by any of the other potential stress factors.